Exploring Patient Pain Experiences during and after Conventional Red Light and Simulated Daylight Photodynamic Therapy for Actinic Keratosis: A Qualitative Interview Study - Alexandra Sjöholm; Magdalena Claeson; John Paoli; Birgit Heckemann (Medical Journals Sweden, 2024)
Simulated daylight photodynamic therapy is a relatively new and potentially less painful alternative to conventional red light photodynamic therapy for actinic keratosis. Qualitative research exploring patient experiences of pain and skin reactions during these treatments is scarce. To address this, semi-structured interviews were conducted of 10 patients aged 60-81 years with symmetrically distributed actinic keratoses 4 weeks after split-face treatment with conventional red light photodynamic therapy and simulated daylight photodynamic therapy. The participants were recruited from an ongoing clinical randomized trial. Interviews (median length 35 min) were conducted between June 2022 and January 2023, audio-recorded, transcribed verbatim, and analysed qualitatively using content analysis, as described by Graneheim and Lundman. Participants reported that conventional red light photodynamic therapy was very painful during illumination and transiently painful in the post-treatment period, while simulated daylight photodynamic therapy was almost painless during illumination and led to minor post-treatment pain. Also, skin reactions were more intense and longer-lasting with conventional red light photodynamic therapy than with simulated daylight photodynamic therapy. Most participants expressed a treatment preference for simulated daylight photodynamic therapy but had reservations about its unestablished long-term effectiveness. This study underscores the considerable pain associated with conventional red light photodynamic therapy, and the pivotal importance of shared decision-making when selecting the most appropriate treatment.